Bibliographie der niederländischen Literatur in deutscher Übersetzung : Niederländische Literatur des 17. Jahrhunderts - Bundschuh-van Duikeren, Johanna, 1979- (Berlin ; Boston : De Gruyter, 2011)
The separation of the Netherlands from the Habsburg Empire in 1581 brought about political and religious independence and the so-called Golden Age in the 17th century, a period of economic and cultural prosperity. Hence, the Netherlands became a magnet for students and scholars from all over Europe. This was also reflected in the translations into German. The bibliography covers more than 1,000 translations, illuminating the various phases of the reception of Dutch texts. For the study of the history of European literary and cultural relations, it is an indispensable reference work. Johanna Bundschuh-van Duikeren, Freie Universität Berlin.
Includes bibliographical references and index
Keywords: Dutch literature -- Translations into German -- Bibliography